Use of skin-bleaching products among Saudi population: Are they aware of their hazards? - Hend M Alotaibi; Raghad M Alharthi; Hanadi M AlMutairi; Alanoud S Alsuhibani; Rakan F Alenezi; Abdulaziz A Alodhayani (Wolters Kluwer Medknow Publications, 2022)
Background: The application of skin-whitening products to have fairer and lighter skin tone has now become common practice worldwide. Research supports that even skin distribution and fairer skin are the symbol of attractiveness and superiority. Objective: This study aims to determine the belief and awareness about the composition and hazardous effects of skin-whitening products among Saudi population. Design: This was a descriptive cross-sectional study. Methods: A total of 395 respondents participated in the study. This was a cross-sectional survey study that was carried out in Riyadh, Saudi Arabia. The two-part questionnaire was filled by a convenience sample of 395 Saudi participants. The survey questions were related to whitening creams effectiveness, reasons of use, and the safety of the whitening products. The survey data were analyzed using SPSS version 21. Results: The most representative age group who responded was 18-25 years (26%), 73% were female (n = 185), and 53.1% were married. Regarding the level of knowledge among respondents on skin-whitening cream-negative implications, it was found that there is an association between age and whitening cream side effects (<0.05). Ages between 18 and 25 (73.5% said yes) and between 31 and 35 (75.6%) suffer higher from side effects of whitening creams as compared to the other age groups. Conclusion: The analysis shows that cosmetic use of skin-whitening creams is more common among females. The people of all age groups were not aware of the deleterious effects of skin-whitening creams. From the study, it was found that people who suffer from the negative effects of creams were mostly of age less than 35.